Comprehensive Evaluation Method of Office Building Energy Consumption Based on Improved Multi-index. Issue 1 (March 2020) - Chai, Kang; Yu, Junqi; Tian, Ying; Zhao, Anjun; Gao, Jiaojiao; Nie, Jikai
Abstract: In view of the imperfection in the selection of energy consumption characteristics and energy conservation evaluation methods, this paper proposes an energy consumption analysis and energy conservation evaluation method suitable for office buildings. Through the analysis of office building energy consumption monitoring layer data, establishing standard of building energy consumption data sets, including office building day by day, month by month, year after year way of energy consumption and heating and cooling is analyzed, and aiming at the problem of building energy efficiency evaluation index weights are difficult to determine the, combined with the feature of energy consumption was proposed to build multiple indexes comprehensive evaluation of energy consumption. Through the example of office building, the evaluation results are verified, which proves that this method can evaluate the energy consumption of buildings reasonably and feasible, and provides a new idea for the comprehensive evaluation of building energy conservation.